Hardware challenges with an anticoagulation strategy guided by detection of atrial fibrillation by an implantable loop recorder. (25th November 2020) - Mittal, S; Brenner, D; Oliveros, S; Bhatt, A; Preminger, M; Sichrovsky, T; Musat, D
Abstract: Background: A "pill-in-the-pocket" anticoagulation strategy, guided by ECG data from an implantable loop recorder (ILR), has been advocated as a clinical strategy. However, a fundamental requirement is the ability to reliably obtain daily ECG data from patients. Objective: To determine the reliability of daily ECG data transfer from ILRs. Methods: We evaluated patients implanted with an ILR in whom we sought to withhold oral anticoagulation (OAC) unless atrial fibrillation (AF) was detected. The ILR transmits data nightly to a bedside monitor. Once received, the data are sent to a central server. Over the course of a month, we tracked for each patient whether ECG data were received by the server. Results: The study included 170 AF patients with an ILR where we planned to withhold OAC unless AF was documented. Daily ECG data were automatically transmitted and retrievable in only 36 (21%) patients. Two (1%) pts had not a single day of connectivity, 6 (4%) pts were connected <7 days, and 16 (9%) pts were connected <14 days. Wireless connectivity was lost for >48 hours in 89 (52%) patients (Figure). Most patients experienced multiple reasons for data transmission failure within the month. Conclusions: To determine whether an ILR guided OAC strategy is feasible, reliable daily transmission of ECG data is a fundamental prerequisite. Current technology facilitated daily ECG data transfer in only 1/5 of patients. In the remaining, there was either extended loss of connectivity or no connectivity at all. A "pill-in-the-pocket" anticoagulation approach is currently difficult given existing hardware limitations. Funding Acknowledgement: Type of funding source: None